Twenty years of research on HTLV-1 and its medical complications in Peru: general perspectives - Gotuzzo Herencia, Eduardo (2010)
The human T-lymphotropic virus type 1 (HTLV-1 [human T-lymphotropic virus]) is a retrovirus with worldwide distribution. Belongs to the Retroviridae family and subfamily Oncovirinae. It is a lymphotropic virus that mainly involves CD4 lymphocytes. The HTLV-1 is related as the etiologic agent of leukemia / lymphoma, adult T-cell (ATLL) and myelopathy / tropical spastic paraparesis (M / PPET).